2019
DOI: 10.3390/app9040660
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Murine Immune Cells upon Co-culture with Plasma-treated B16F10 Melanoma Cells

Abstract: Recent advances in melanoma therapy increased median survival in patients. However, death rates are still high, motivating the need of novel avenues in melanoma treatment. Cold physical plasma expels a cocktail of reactive species that have been suggested for cancer treatment. High species concentrations can be used to exploit apoptotic redox signaling pathways in tumor cells. Moreover, an immune-stimulatory role of plasma treatment, as well as plasma-killed tumor cells, was recently proposed, but studies usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 99 publications
3
29
0
Order By: Relevance
“…[ 8 ] The current concept is that these plasma‐derived ROS generate secondary ROS and oxidation products that accumulate inside tumor cells, leading to mitochondrial damage [ 24 ] and pro‐apoptotic signaling. [ 25 ] Exposure of tumor cells to plasma‐derived ROS is accompanied by changes in the release of chemokines and cytokines, [ 26 ] several immunomodulatory receptors, [ 27 ] and upregulation of markers of the immunogenic cancer cell death (ICD) [ 28 ] and cellular senescence. [ 29 ] While many reports point to a selectivity of gas plasma treatment to induce toxic effects in tumor cells over non‐malignant cells, [ 30–33 ] more comprehensive studies revealed that selectivity depended on the type of tumor cell investigated and the cell line used for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] The current concept is that these plasma‐derived ROS generate secondary ROS and oxidation products that accumulate inside tumor cells, leading to mitochondrial damage [ 24 ] and pro‐apoptotic signaling. [ 25 ] Exposure of tumor cells to plasma‐derived ROS is accompanied by changes in the release of chemokines and cytokines, [ 26 ] several immunomodulatory receptors, [ 27 ] and upregulation of markers of the immunogenic cancer cell death (ICD) [ 28 ] and cellular senescence. [ 29 ] While many reports point to a selectivity of gas plasma treatment to induce toxic effects in tumor cells over non‐malignant cells, [ 30–33 ] more comprehensive studies revealed that selectivity depended on the type of tumor cell investigated and the cell line used for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Within the tumor microenvironment, they recognize tumor antigens and lyse the target cells, helping the body to fight cancer using its endogenous weapons provided by the immune system. Using direct plasma treatment or plasma-conditioned liquids, ICD has been observed in vitro in a number of tumor cell types including, for instance, pancreatic cancer, colorectal cancer, lung cancer, and malignant melanoma [99,[131][132][133][134][135][136][137][138][139][140]. Due to the extensive poly-pragmasia of plasma sources used in the field of plasma medicine, the central mechanisms underlying plasma-induced ICD have not been commonly unraveled.…”
Section: Induction Of An Immune Response Through Cap Treatmentmentioning
confidence: 99%
“…Instead, the gas plasmas act via the local deposition of a plethora of reactive oxygen species (ROS) [16] that promote cancer cell death [17]. Previous studies suggested that plasma-induced tumor toxicity also has an immunogenic component [18][19][20], leading to antitumor immunity in vivo [21][22][23]. Specifically, it was observed that plasma treatment leads to an increased expression of calreticulin, a protein that dictates the immunogenicity of cells [24].…”
Section: Introductionmentioning
confidence: 99%